2008
DOI: 10.1242/dev.015263
|View full text |Cite
|
Sign up to set email alerts
|

The role of Broad in the development ofTribolium castaneum:implications for the evolution of the holometabolous insect pupa

Abstract: The evolution of complete metamorphosis in insects is a key innovation that has led to the successful diversification of holometabolous insects, yet the origin of the pupa remains an enigma. Here, we analyzed the expression of the pupal specifier gene broad (br), and the effect on br of isoform-specific, double-stranded RNA-mediated silencing, in a basal holometabolous insect, the beetle Tribolium castaneum. All five isoforms are weakly expressed during the penultimate instar and highly expressed during the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
130
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(136 citation statements)
references
References 34 publications
6
130
0
Order By: Relevance
“…These data suggested that the moderate levels of BR-C mRNAs, detectable during premetamorphic stages in both species, had no essential role. This scenario would agree with the fact that zygotic BR-C function is not required in Drosophila BR-C null nonpupariating mutants until the onset of metamorphosis (Belyaeva et al, 1980;Kiss et al, 1988), and with recent data on Tribolium (Suzuki et al, 2008). However, as neither RNAi nor the likely hypomorphic TcBR-C KS342 allele present a complete loss-of-function situation, we cannot exclude a possibility that BR-C plays some additional role, not visualized by our phenotypes.…”
Section: Role Of Br-c In Temporal Tissue Coordination During Metamorpsupporting
confidence: 89%
See 1 more Smart Citation
“…These data suggested that the moderate levels of BR-C mRNAs, detectable during premetamorphic stages in both species, had no essential role. This scenario would agree with the fact that zygotic BR-C function is not required in Drosophila BR-C null nonpupariating mutants until the onset of metamorphosis (Belyaeva et al, 1980;Kiss et al, 1988), and with recent data on Tribolium (Suzuki et al, 2008). However, as neither RNAi nor the likely hypomorphic TcBR-C KS342 allele present a complete loss-of-function situation, we cannot exclude a possibility that BR-C plays some additional role, not visualized by our phenotypes.…”
Section: Role Of Br-c In Temporal Tissue Coordination During Metamorpsupporting
confidence: 89%
“…BR-C in both cases promotes the pupal fate (Zhou and Riddiford, 2002), and therefore JH must regulate BR-C differently in larvae and in pupae. In lepidopteran (Zhou et al, 1998;Reza et al, 2004), as well as in Tribolium (Suzuki et al, 2008) larvae, JH prevents BR-C expression until the onset of metamorphosis, and presumably that is how JH prevents pupal differentiation. Conversely, removal of the JH source (allatectomy) causes both BR-C misexpression and precocious pupal development.…”
Section: Regulation Of Br-c By Met-dependent Jh Signalingmentioning
confidence: 99%
“…Therefore, our mosaic analysis of broad suggests that the larval epidermal cells are not pupally committed in the absence of broad, and thus they repeat larval-larval molts, although the hosts metamorphosed into pupae and adults. These results clearly indicate that broad is essential for the juvenile-adult transition in Bombyx, as found in other holometabolous insects (19,21,(41)(42)(43)(44)(45). Given the results of mosaic analysis, we further examined the expression of broad mRNAs in JH-deficient and JH signalingdeficient mutant Bombyx (Fig.…”
Section: Significancementioning
confidence: 52%
“…In contrast, fenoxycarb treatment induced the expression of BR-C Z2, BR-C Z4 and BHR3 at the same stage of development. According to previous studies on holometabolous insects, high levels of JH are correlated with a low expression of BR-C and a prolonged expression of them in treated insects during the late prepupal stage may due to high levels of 20E in the presence of JH (Zhou et al, 1998;Suzuki et al, 2008). According to these results, the patterns in the expression of BRC isoforms are similar to that recorded in M. sexta, D. melanogaster and A. aegypti (Wu et al, 2006) in which the application of juvenile hormone analogues causes their re-expression.…”
Section: Discussionmentioning
confidence: 87%